Administration of a novel plant extract product via drinking water to post-weaning piglets: effects on performance and gut health. (17th April 2014) - Bontempo, V.; Jiang, X. R.; Cheli, F.; Lo Verso, L.; Mantovani, G.; Vitari, F.; Domeneghini, C.; Agazzi, A.
Abstract : The present study evaluated the effects of a novel plant extract (PE) product (Grazix TM ) on the performance and gut health of weaned piglets challenged with Escherichia coli. The PE was a standardised mixture of green tea leaves ( Camellia sinensis ) and pomegranate fruit ( Punica granatum ) obtained by using the LiveXtract TM process. A total of 144 piglets were weaned at 24 days and allocated to 8 for a 35-day experiment with a 2×2×2 factorial design comparing different treatments (water without product (CT) or 8 μl/kg per day PE in drinking water (PE)), feeding regimens ( ad libitum (AD) or restricted (RE)) and oral E. coli challenges on day 9 (sham (−) or infected (+)). There were six pens per group with three piglets per pen. On day 35, 24 of the RE feeding piglets were slaughtered. It was found that PE supplementation increased the average daily gain (ADG) from day 28 to day 35 ( P =0.03) and increased the gain to feed ratio (G : F) from day 7 to day 14 ( P =0.02). RE feeding led to lower feed intake in piglets during the 1 st week ( P <0.01), 2 nd week ( P =0.06), 3 rd week ( P =0.05), and throughout the course of the overall study period ( P =0.05). E. coli challenge decreased the ADG and G : F ratio from day 7 to day 14 ( P =0.08 and <0.01, respectively) and increased the faecal score (higher values indicate more severe diarrhoea) on days 14, 21, 28 and 35 ( P <0.01). PE supplementation decreased the faecal score in the challenged piglets during the 1 st week post-challenge ( P <0.01). E. coli challenge increased the faecal E. coli level on day 14 ( P =0.03) and increased the Enterobacteriaceae level on day 35 ( P <0.01). Reduced faecal E. coli was observed on days 14 and 35 ( P =0.05 and 0.02, respectively), and reduced Enterobacteriaceae ( P <0.01) was found on day 35 in the PE animals. RE feeding increased the faecal Lactobacillus, Enterobacteriaceae and E. coli levels on day 35 ( P =0.02, <0.01 and <0.01, respectively). These results suggest that PE supplementation may improve the gut health status of post-weaning piglets and counteract some of the negative effects that occur when piglets are challenged with E. coli.